Shot put: Biomechanical analysis Gill Jacko 19,98m 20,01m 7kg - Poppe, D.
A unique document by Didier POPPE and this will be probably one of the most interesting videos of this web site for coaches and athletes interested by the rotational shot put and who want to know why the young Jacko GILL is so good . Of course he does not have a perfect technique (who has ?) and his start and torque could be improved (He is working on it) , BUT, his technique is very well suited to his athletics specificity and the expert eyes will soon pick the datas which make the difference during the building momentum , transfer and delivery phases with a minimal suspension time , super fast right left landings , and acceleration in the throwing path. Of course , the video document quality and Dartfish software used for this analysis are not perfect and subject to some error margin , but it does not change anything on the conclusions one can draw out of this document and the specificity of this incredible thrower who is destroying not only world records but also many commonly accepted "clichés" that people have on the shot put high performance approach.